Phytochemical screening, antimicrobial and cytotoxicity studies of Heritiera fomes - Tabassum, Rifah (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2020.